Comportamente culturale și identități multiple (Romanian Studies Today, 2024)
The present study is an integral part of a research project which has as its motivation and starting point a series of didactic and methodological aspects, difficulties and challenges encountered in the teaching of Romanian as a foreign language (RLS) in universities abroad, in particular to Romanian origin students.My interest in these issues is relatively recent and focuses mainly on them not from a strictly sociological and/or sociolinguistic point of view, as phenomena in themselves, but rather I study and analyze them from the perspective of trying to define some theoretical coordinates for the context behind the teaching reality I am facing – a constantly increasing number of students of Romanian origin, who came to Italy at a young and very young age or even born here, who belong to the Romanian community and are therefore basically native speakers (heritage language), and who nevertheless enrol to study the specialization "Romanian language" at Sapienza University, where Romanian is taught as a foreign language. I will try to analyze to what extent the linguistic-cultural behavior is determined, in the case of these students, by their multiple ethnic and/or linguistic identity due to the migration phenomenon.
Keywords: behaviour; identity; cultural identity; migration; cultural integration